Parody and Contrafaction in the Cantigas by Alfonso X - Ferreira, Manuel Pedro Ramalho (2014)
Contrafaction, allusion and parody are related concepts, yet the extent to which they can be applied in song before 1300 is very different. This paper explores the uses of contrafactum in early Iberian song, from the time of the Emirate of Cordoba onwards, and examines in detail Galician -Portuguese cantigas by Alfonso X (+1284), of both secular and devotional nature, trying to determine the presence of such procedures. Cantigas de Santa Maria include nr. 90 (compared with the responsory Gaude Maria Virgo); 350 (compared with the sequence Dies irae); 422 (compared with the Song of the Sibyl); 421 (compared with the offertory Recordare, Virgo Mater); 340 (compared with the alba S'anc fui belha by Cadenet); 132 (compared with Alfonso's satyre Nom me posso pagar tanto). Other cantigas include the debate of Alfonso with Arnaut, Senher, ad-ars ie'us venh' querer (confronted with Can vei la lauzeta mover by Bernart de Ventadorn) and the former's satirical song Com'eu en dia de Pascoa (which recalls the Latin Kyrie Cunctipotens genitor).